Heat Tolerance Stability of Bread Wheat Genotypes under Early and Late Planting Environments through Stress Selection Indices - Ahmad, Zeeshan; Ishaq, Muhammad; Tahir, Iqra; Khan, Adeel; Jehan, Kainat (Current Research in Agricultural Sciences, 2021)
A field study was conducted with an objective to assess thirty six wheat cultivars for tolerance, stability and enhancing productivity under optimum and stressed planting environments at Cereal crops Research Institute (CCRI), Nowshera, Pakistan during 2017-18. Experiment was laid out in randomized complete block design using three replications. Pool analysis of variance exhibited highly significant (p≤0.01) variations among wheat genotypes, environments and G × E interactions for the under studied traits. In general, reduction in mean wheat genotypes for days to heading (19%) and grain yield (65%) was observed under stressed condition as compared to optimum planting environment. Across planting environments, highest grain yield was produced by wheat genotypes Pakistan-13 (3746 kg ha-1) closely followed by two other genotypes Zincol-2016 (3712 kg ha-1) and PR-122 (3671 kg ha-1). Various stress selection indices viz tolerance (TOL), mean productivity (MP), harmonic mean (HM), geometric mean productivity (GMP), stress tolerance index (STI), yield index (YI), stress susceptibility index (SSI) and yield stability index (YSI) were employed for each genotype under both environments. Correlation coefficient analysis unveiled that days to heading and grain yield had positive significant association with GM, HM MP, YI and STI. Aforementioned stress selection indices were found effective tools for identification of stress tolerant genotypes under delayed planting. On the basis of these selection indices, wheat genotypes i-e Zincol-16, Pirsabak-13, PR-122 and Pakistan-13 were found high yielding stress tolerant which could be sown under non-stressed and stressed conditions and could be used in future wheat breeding schemes.